Belowground Biomass Carbon Density in Xinjiang Grasslands: Spatiotemporal Variability and Dominant Drivers - Ping Dong; Changqing Jing; Gongxin Wang; Yuqing Shao (Agronomy)
Arid grasslands exhibit high proportions of belowground biomass (BGB), yet the climatic influence on BGB carbon density remains poorly understood. Accurately estimating BGB carbon density in arid grassland vegetation presents a significant challenge. Using extensive field sampling, multi-source remote sensing data, and machine learning methods, the spatial distribution of BGB carbon density across Xinjiang grasslands was estimated, and its environmental drivers across different geomorphological regions were revealed. The results show that BGB carbon density accounts for 93.8–97.2% of total carbon density in Xinjiang grassland, with notably high proportions exceeding 97% in the Junggar Basin, Kunlun Mountains, and Altun Mountains regions. From 2000 to 2023, BGB carbon density increased significantly (p < 0.01) from 1175.18 gC·m−2 to 1379.09 gC·m−2, with significant increases observed in the Junggar Basin, Tarim Basin, Kunlun Mountains, and Altun Mountains. In addition, environmental factor analysis revealed distinct soil moisture threshold effects governing BGB carbon density-precipitation relationships: carbon density increases linearly with precipitation when soil moisture remains below 0.2 m3·m−3, shows a parabolic relationship between 0.2 and 0.4 m3·m−3, and decreases with increasing precipitation when soil moisture exceeds 0.4 m3·m−3. Soil moisture and precipitation emerge as dominant factors influencing BGB carbon density changes, with regional variations in their relationships. These findings provide critical insights into carbon sequestration dynamics in arid grassland ecosystems and their response mechanisms under climate change.